STUDY AND DISTRIBUTION IN OIL PORTS SHALLOWING SEDIMENTS (OIL WHARVES) PT CALTEX PACIFIC INDONESIA DUMAI, RIAU 1990 POST-DREDGING - Hendra Yusran Siry (Pusbindiklat - LIPI, 2011)
To study the process of rapid sedimentation occurred required an understanding of the characteristics of the sediments and oceanographic processes. This paper is to analyse source of silting up and sediment distribution surrounding oil wharves of PT Caltex Paciﬁ c Indonesia (PT CPI) after big dredging in 1990 during four months research and intensive survey in 18 research sampling areas. The research used gravimetric method for sediment samples identiﬁ cation and ﬁ eld survey for oceanographic conditions twice sampling time, ﬂ ood tide and ebb ﬂ ood. Data showed sediment fraction consist of sandy mud with 48.175–74.735% mud content. Classiﬁ cation and result of sediment statistic analysis indicated wave energy and tide caused silting-up process in the surrounding PT CPI’s oil wharves. This process was sped up by the environmental conditions, reclamation and coastal land changes.